Core technology from Maripe Cave site (Santa Cruz, Argentina): Implications for rocks provisioning processes and lithic production. (21st July 2015) - Hermo, Darío; Lynch, Virginia
Abstract: This paper discusses provisioning strategies of lithic raw materials at Maripe Cave site (province of Santa Cruz, Argentina). The archaeological sequence represents different moments of human occupation at the cave and in the study area, which show different lithic technologies. The morpho-typological analysis of the lithic cores recovered contributes to our knowledge about the strategies related to procurement and provisioning of the lithic raw materials used for artifacts production. We identified different raw materials from the analyses of lithic cores and other artifacts from the site. This allowed analyzing trends in selection and provisioning processes and interpreting the mobility strategies of the groups that inhabited the Deseado Massif since the Pleistocene–Holocene transition. Trends suggest that, during the Pleistocene–Holocene transition and early Holocene, abandoned cores from Maripe Cave mainly indicate people provisioning strategies. During middle Holocene, the cores shows blades extractions and raw material use from long distance, discarded with remaining potential utility. Finally, at late Holocene the cores were mainly prepared for blade extractions. Our results do not fully agree with Kuhn's proposal, probably due to both the theoretical polarization between the provisioning strategies and the palimpsest effect.